The Encouragement of Teacher’s Descriptive Notes in Student Report Card - Aloysius Mering; Indri Astuti; Fadillah Fadillah (Journal of Educational Science and Technology (EST), 2019)
This study aimed to (a) describe aspects in descriptive notes that teachers do on student report cards, (b) describe the efforts of teachers in making descriptive notes on student report cards, and (c) examine the teacher's encouragement power in descriptive notes on report cards against students. The research information was obtained through survey method towards teachers, students, and parents in Gembala Baik Senior High School, SantunUntan Senior High School, and Senior high school in Sukadana, Kayong Utara district, in the form of questionnaire, interview, and documentation. From the result of the study it could be explained that teachers have written the aspects of knowledge, skills, and attitudes in student report cards balanced in the descriptive record, the teacher mentioned: the name of the student, behavior, things that need improvement, attitude, saying "congratulations", avoiding negative labels, and encouraging words. In addition, “Some teachers” let the application provided to make the descriptive notes. Moreover, only "a small part" of the teacher who was convinced that the notes have encouraged students actually. Therefore, the descriptive notes was “less effective”